DEFB1 polymorphisms and susceptibility to recurrent tonsillitis in Italian children. - Zupin, Luisa; Polesello, Vania; Grasso, Domenico Leonardo; Crovella, Sergio; Segat, Ludovica (Int J Pediatr Otorhinolaryngol, 2016)
INTRODUCTION: The tonsils are secondary lymphoid organs fundamental for immune system response against pathogens within the oral cavity. Tonsillitis refers to inflammation of the pharyngeal tonsils that may include the adenoids and the lingual tonsils and that can be acute, recurrent, and chronic. Viral or bacterial infections, as well as immunologic factors are the main trigger to tonsillitis and disease's chronicity: the host immune responses, especially the innate one, could play an important role in susceptibility to the disease. OBJECTIVES: The current study aims at investigating the role of functional polymorphisms in the 5'UTR (c.-52G>A, c.-44G>C and c.-20G>A) of DEFB1 gene, encoding for the antimicrobial peptide human beta-defensin 1, in the predisposition to recurrent tonsillitis in children from North Eastern Italy. RESULTS: No significant correlation was found between DEFB1 allele, genotype and haplotype frequencies and recurrent tonsillitis susceptibility with the exception of an increased risk to disease development in patients carrying DEFB1 rare haplotypes. CONCLUSION: Our results may suggest that DEFB1 polymorphisms alone may not influence pathology susceptibility, however they could possibly concur, together with other factors involved in the genetic control of innate immune system, in the predisposition towards recurrent tonsillitis.